(untitled) (Research, Society and Development, 2021)
Dental agenesis consists of an anomaly characterized by the numerical reduction of dental elements and, according to the number of missing teeth, it may receive other names, such as hypodontia, oligodontia, anodontia or congenital absence. Several treatments may be recommended depending on the patient’s needs and conditions, such as surgery for the installation of implants and fixed prostheses, and early diagnosis is one of the key parts for proper treatment. The rehabilitation of agenesis of the upper lateral incisor is a great challenge for the professional since several factors can influence the aesthetic result and, in addition, the absence of the dental element can bring unbalance of the occlusion and phonetic problems. It is essential to carry out an adequate planning and a treatment plan with multidisciplinary action so that the final result is effective and meets the expectations of each patient. The present study aimed to report a clinical case of dental agenesis of the upper lateral incisor, where the treatment of choice was the installation of an implant-supported prosthesis and filling of the buccal bone plate with biomaterial.